Impact of the volume and the profile of volatile fatty acids in the rumen fermentation on cow productivity and milk composition - Mikołajczyk, Katarzyna (Array, 2019)
The aim of the research was to establish relations between the selected rumen fermentation products and the milk composition in dairy cows. The experiment was conducted on 10 Polish Holstein-Friesian cows of black and white variety. The animals were kept in the free stall housing system and fed with the total mixed ration (TMR). The herd’s milk production was assessed using the A4 method and the milk analyses were obtained from the milk recordings. The rumen digesta were sampled two hours after the morning delivery of TMR using a stomach pump. The sampled digesta were diluted with buffer, homogenized and the obtained suspension was analysed using gas chromatograph with the FID detector to determine the total concentration of volatile fatty acids (VFA) and the percentage of individual VFAs. Milk composition was obtained from the RW-1 reports, and the Pearson correlation coefficient was calculated for the obtained parameters. It was determined that propionate and the relation of propionate to butyrate in the rumen digesta increased the protein content and its fractions in milk. The volatile fatty acids utilization coefficient in the rumen digesta a positive correlation to protein contents and a negative correlation to the level of caseins in milk were shown. Processes taking place in the cow rumen significantly influence the composition and quality of milk. The knowledge of volatile fatty acids content and the of individual VFAs allows for the management of the rumen fermentation in order to obtain better technological parameters of milk.